The Influence of Promotion, Price and Religiusity on The Purchasing Decision of Beauty Products Halal Labeled - Mila Mila; Noer Aisyah Barlian (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
Marketing includes advertising, selling and delivering products to consumers or other companies. In carrying out promotions, they will target people who are in accordance with the products being marketed. Not only that, in marketing, the part that has this task will make attractive packaging or designs in advertisements so that many people will be interested. In addition, marketing is also very helpful for consumers. The research objectives of this study are: to explore the influence between promotions on purchasing decisions for beauty products labeled halal. to explore the influence between prices and purchasing decisions of beauty products labeled halal. to explore the influence between religiosity with the decision to purchase beauty products labeled halal. This research uses quantitative research methods. Data collection techniques using documentation and questionnaires. as for data analysis using multiple Linear Regression. The conclusions from this study are: There is an influence between the promotion variables on the purchasing decision of beauty products labeled halal. This means that the better the promotion can affect the purchasing decision. There is an influence between the price variable on the purchasing decision of beauty products labeled halal. There is no influence between the religiosity variable on the decision to purchase beauty products labeled halal. This means that the high and low religiosity of IAI students has no influence on the decision to purchase beauty products labeled halal.